Partial pressure of arterial carbon dioxide after resuscitation from cardiac arrest and neurological outcome: A prospective multi-center protocol-directed cohort study. (February 2019) - Hope Kilgannon, J.; Hunter, Benton R.; Puskarich, Michael A.; Shea, Lisa; Fuller, Brian M.; Jones, Christopher; Donnino, Michael; Kline, Jeffrey A.; Jones, Alan E.; Shapiro, Nathan I.; Abella, Benjamin S.; Trzeciak, Stephen; et al.
Abstract: Aims: Partial pressure of arterial carbon dioxide (PaCO2 ) is a regulator of cerebral blood flow after brain injury. We sought to test the association between PaCO2 after resuscitation from cardiac arrest and neurological outcome. Methods: A prospective protocol-directed cohort study across six hospitals. Inclusion criteria: age ≥18, non-traumatic cardiac arrest, mechanically ventilated after return of spontaneous circulation (ROSC), and receipt of targeted temperature management. Per protocol, PaCO2 was measured by arterial blood gas analyses at one and six hours after ROSC. We determined the mean PaCO2 over this initial six hours after ROSC. The primary outcome was good neurological function at hospital discharge, defined a priori as a modified Rankin Scale ≤3. Multivariable Poisson regression analysis was used to test the association between PaCO2 and neurological outcome. Results: Of the 280 patients included, the median (interquartile range) PaCO2 was 44 (37–52) mmHg and 30% had good neurological function. We found mean PaCO2 had a quadratic (inverted "U" shaped) association with good neurological outcome, with a mean PaCO2 of 68 mmHg having the highest predictive probability of good neurological outcome, and worse neurological outcome at higher and lower PaCO2 . Presence of metabolic acidosis attenuated the association between PaCO2 and good neurological outcome, with a PaCO2 of 51 mmHg having the highest predictive probability of good neurological outcome among patients with metabolic acidosis. Conclusion: PaCO2 has a "U" shaped association with neurological outcome, with mild to moderate hypercapnia having the highest probability of good neurological outcome.